Effects of subcutaneous injection of ozone during wound healing in rats. (4th March 2019) - Soares, Ciro D.; Morais, Thayná M. L.; Araújo, Roberta M. F. G.; Meyer, Patrícia F.; Oliveira, Eric A. F.; Silva, Rodrigo M. V.; Carreiro, Eneida M.; Carreiro, Edvaldo P.; Belloco, Verônica G.; Mariz, Bruno A. L. A.; Jorge-Junior, Jacks
Abstract: Fibroblast growth factor 2 (FGF2) regulates the wound repair process and it is secreted by inflammatory and endothelial cells, and by myofibroblasts. This study aimed to establish the expression patterns of FGF2 and myofibroblastic differentiation during wound healing in rats treated with subcutaneous ozone injection. We created full-thickness excisional wounds in rats, and the healing process was analyzed through morphometric analyses and digital quantification of immunoreactivity of smooth muscle actin and FGF2. Ozone therapy-treated wounds presented granulation tissue with a reduced number of inflammatory cells and greater dermal cellularity, and intense collagen deposition. FGF2 immunoreactivity, microvessel density, and amount of myofibroblasts were significantly higher in treated wounds compared to controls. In conclusion, it was demonstrated that subcutaneous injections of ozone accelerate and ameliorate wound repairing process. Moreover, injectable ozone therapy's action mechanism may be associated with FGF2 overexpression.